Communication Barriers and Digital Technology Readiness in Inclusive Elementary Schools: A Thematic Analysis of Stakeholder Perspectives on Teacher-Parent Interaction for Children with Special Needs - Yuliansyah, Arief; Rusmana, Nandang; Abdul Rozak, Rama Wijaya (Jurnal Paedagogy, 2026)
This study aims to investigate the communication barriers and digital technology readiness of classroom teachers, special education companion teachers (GPKs), and parents of children with special needs (ABK) at SD Laboratorium UPI Cibiru, Bandung Regency. A qualitative approach was employed using semi-structured, in-depth interviews with 60 participants, comprising 18 classroom teachers, 19 special education companion teachers (GPKs), and 23 parents. The data were analyzed thematically using NVivo 15 software. The findings revealed six interconnected themes: (1) current communication practices dominated by WhatsApp; (2) multidimensional communication barriers encompassing structural, technical, and relational factors; (3) unmet needs for structured digital communication features; (4) stakeholders' perceptions of and readiness for website-based platforms; (5) concerns regarding the security and privacy of ABK students' data; and (6) the critical importance of long-term developmental documentation. The findings indicate that, although WhatsApp is universally used, it fails to support the structured, secure, and longitudinal communication required for effective inclusive education. Stakeholders across all participant groups demonstrated moderate-to-high levels of digital readiness, providing a strong foundation for the adoption of purpose-built digital communication platforms. These findings have important implications for the design of educational technologies and the development of inclusive education policies in Indonesia.